2008
DOI: 10.1523/jneurosci.1648-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Central Respiratory Rhythmogenesis Is Abnormal inLbx1- Deficient Mice

Abstract: Lbx1 is a transcription factor that determines neuronal cell fate and identity in the developing medulla and spinal cord. Newborn Lbx1 mutant mice die of respiratory distress during the early postnatal period. Using in vitro brainstem-spinal cord preparations we tested the hypothesis that Lbx1 is necessary for the inception, development and modulation of central respiratory rhythmogenesis. The inception of respiratory rhythmogenesis at embryonic day 15 (E15) was not perturbed in Lbx1 mutant mice. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 43 publications
9
90
1
1
Order By: Relevance
“…Here, we strengthen the case for the RTN as principal chemosensor by showing that central chemosensitivity is lost in two additional mutations that affect the RTN but leave intact other candidate chemosensors. The CO 2 /pH responsiveness of other mutants affecting the RTN was either not explored in Lbx1 mutants (Pagliardini et al, 2008) or found to be preserved in vivo in Egr2 mutants (Jacquin et al, 1996). The latter result contrasts with the complete lack of chemosensitivity observed here in brainstem preparations of Egr2 cre ;Phox2b lox/lox embryos.…”
Section: Lack Of Co 2 /Ph Responsiveness In Phox2b Mutantscontrasting
confidence: 79%
See 4 more Smart Citations
“…Here, we strengthen the case for the RTN as principal chemosensor by showing that central chemosensitivity is lost in two additional mutations that affect the RTN but leave intact other candidate chemosensors. The CO 2 /pH responsiveness of other mutants affecting the RTN was either not explored in Lbx1 mutants (Pagliardini et al, 2008) or found to be preserved in vivo in Egr2 mutants (Jacquin et al, 1996). The latter result contrasts with the complete lack of chemosensitivity observed here in brainstem preparations of Egr2 cre ;Phox2b lox/lox embryos.…”
Section: Lack Of Co 2 /Ph Responsiveness In Phox2b Mutantscontrasting
confidence: 79%
“…By genetic tracing, partnering either the Lbx1 cre or the Egr2 cre allele with the Tau GFPnLacZ reporter, we first confirmed published evidence (Pagliardini et al, 2008;Thoby-Brisson et al, 2009) that the majority of RTN neurons arise from the Lbx1 cre -expressing domain of the alar plate (Sieber et al, 2007), in the Egr2 creexpressing r3 or r5 (Voiculescu et al, 2001) (Fig. 3A-J (Fig.…”
Section: Rtn Development Depends On Phox2bsupporting
confidence: 75%
See 3 more Smart Citations